KARAKTERISTIK DASAR ANAK DENGAN SPEECH DELAY DI POLI TUMBUH KEMBANG RSUD DR.SOETOMO SURABAYA PADA PERIODE JANUARI 2017 HINGGA DESEMBER 2017 - Kurniasari, Anggun Febry; Suryawan, Ahmad; Utomo, Budi (Universitas Tribhuwana Tunggadewi, 2021)
Speech and language skills are important in all developments in children. Dr. Soetomo Surabaya is a Hospital reference in handling speech delay cases but there is no complete and detailed data, especially in child growth and development divition. This study uses descriptive studies in a cross-sectional way. The subject used is the data of children's medical records with the final diagnosis of speech delay in growing and development divition dr. Soetomo Surabaya January 2017 to December 2017 period . That meets the criteria by consecutive sampling. The result , most children with speech delay in growth and developmental divition RSUD Dr.Soetomo Surabaya January 2017 to December 2017 period with male domination gender 73.4%, middle age 33 months 34.4%, the last education of mothers high rate 59.4%, parent jobs private employees 56.2% , the order of the 2nd child 43.8%, came with a major complaint can not speak 42.2%. The most demographic aspects of the male gender, the middle grade of 33 months of age, the work of private employees parents, highly educated parents, the order of the second and dominated children come with complaints of not being able to speak.Keywords : Children, Characteristic , Speech delay